Blockchain in internet‐of‐things: a necessity framework for security, reliability, transparency, immutability and liability. Issue 19 (1st December 2019) - Tariq, Usman; Ibrahim, Atef; Ahmad, Tariq; Bouteraa, Yassine; Elmogy, Ahmed
Abstract : Blockchain is a distributed operation and information supervision technology programmed initially for Bitcoin cryptocurrency. The awareness in Blockchain technology is rapidly growing since the notion was invented in the year 2008. The motivation for the concentration in Blockchain is its significant characteristics that deliver security, privacy, and information reliability devoid of any additional system regulating the communications, and consequently it generates fascinating research domains, specifically from the viewpoint of methodological difficulties and restrictions. This study discovers the wide‐ranging Blockchain technology and studies it's perspective with respect to ' internet‐of‐things' controlled nodes. A resilient prototype method has been programmed that reveals a basic system exhausting Blockchain. The outcome illustrates that the established method is functional in test‐bed environment.